Choosing Wisely Together: Physical and Occupational Therapy Consultation for Acute Neurology Inpatients. (April 2018) - Probasco, John C.; Lavezza, Annette; Cassell, Andre; Shakes, Tenise; Feurer, Angie; Russell, Holly; Sporney, Hilary; Burnett, Margie; Maritim, Chepkorir; Urrutia, Victor; Puttgen, H. Adrian; Friedman, Michael; et al.
Background: Although many hospitalized neuroscience patients have physical and occupational therapy (rehabilitation) needs, patients with none or minimal physical impairments frequently receive rehabilitation consultation, diverting from patients with greatest need. Methods: A multidisciplinary team on the general and cerebrovascular neurology acute inpatient services mapped the rehabilitation consultation process, resulting in multiple implemented interventions including physician education on appropriate acute rehabilitation consultations, modification of multidisciplinary rounds, and discussion of patient rehabilitation needs throughout hospitalization. Nurses used the same functional impairment measurement tool used by physical and occupational therapists, the Activity Measure for Post-Acute Care Inpatient Short Forms (Basic Mobility and Activity domains). Results: The rate for initial rehabilitation consults for patients with no limitations in mobility or activity during the 6-month baseline period was 12%, which was decreased to 7% and 10% during the 6-month intervention and sustain periods, respectively ( P < .001). The baseline rate for patients with no limitations receiving both physical therapy and occupational therapy consultations was 62% and was decreased to 21% and 39% in the intervention and sustain periods, respectively ( P < .001). Rehabilitation sessions per hospital day increased for patients with high functional impairments, from 0.52 at baseline to 0.64 in the intervention and 0.66 in the sustain periods ( P = .02), which equated to 1 more rehabilitation visit per patient hospitalization. Conclusions: A multifaceted intervention led to improved utilization of acute inpatient rehabilitation consultation while increasing the frequency of rehabilitation treatment for patients with highest functional impairment.